The Role of Morphology of the Thumb in Anthropomorphic Grasping: A Review - Nanayakkara, Visakha K.; Cotugno, Giuseppe; Vitzilaios, Nikolaos; Venetsanos, Demetrios; Nanayakkara, Thrishantha; Sahinkaya, M. Necip (Frontiers in Mechanical Engineering, 2017)
The unique musculoskeletal structure of the human hand brings in wider dexterous capabilities to grasp and manipulate a repertoire of objects than the non-human primates. It has been widely accepted that the orientation and the position of the thumb plays an important role in this characteristic behavior. There have been numerous attempts to develop anthropomorphic robotic hands with varying levels of success. Nevertheless, manipulation ability in those hands is to be ameliorated even though they can grasp objects successfully. An appropriate model of the thumb is important to manipulate the objects against the fingers and to maintain the stability. Modeling these complex interactions about the mechanical axes of the joints and how to incorporate these joints in robotic thumbs is a challenging task. This paper presents a review of the biomechanics of the human thumb and the robotic thumb designs to identify opportunities for future anthropomorphic robotic hands.